Different latex production between hilly areas and flat areas in Malacca / Mohamad Farid Rosli - Rosli, Mohamad Farid (Faculty of Plantation and Agrotechnology, 2016)
The impact of slope in latex production of rubber is important as it affects the latex production in profitable. The aim of the current study was to identify the effect of topography in latex production. This study was conducted at Felcra Bukit Sedanan where there are two different areas which are Bukit Seraya and Bukit Sedanan. In this study, latex production, overall cost production and also rainfall reading was collected through estate log books and also from estate database from January 2014 until December 2015. The secondary data then was analyzed by using one way ANOVA. Result showed that average production of latex in flat area was higher than the hilly area for 24 month of data. In addition, the overall cost management in flat area was higher than flat area. However, different latex production might come from another factor such as nutrient level and also water potential on soil.